Identifying the Key Elements of Racially Concordant Care in a Freestanding Birth Center. (2nd August 2019) - Karbeah, J'Mag; Hardeman, Rachel; Almanza, Jennifer; Kozhimannil, Katy B.
Abstract : Introduction: There is empirical evidence that the quality of interpersonal care patients receive varies dramatically along racial and ethnic lines, with African American people often reporting much lower quality of care than their white counterparts. Improving the interpersonal relationship between clinicians and patients has been identified as one way to improve quality of care. Specifically, research has identified that patients feel more satisfied with the care that they receive from clinicians with whom they share a racial identity. However, little is known about how clinicians provide racially concordant care. The goal of this analysis was to identify the key components of high‐quality care that were most salient for African American birthworkers providing perinatal care to African American patients. Methods: We conducted semistructured interviews (30 to 90 minutes) with clinicians (N = 10; midwives, student midwives, and doulas) who either worked at or worked closely with an African American‐owned birth center in North Minneapolis, Minnesota. We used inductive coding methods to analyze data and to identify key themes. Results: Providing racially concordant perinatal care to African American birthing individuals required clinicians to acknowledge and center the sociocultural realities and experiences of their patients. Four key themes emerged in our analysis. The first overarching theme identified was the need to acknowledge how cultural identity of patients is fundamental to the clinical encounter. The second theme that emerged was a commitment to racial justice. The third and fourth themes were agency and cultural humility, which highlight the reciprocal nature of the clinician‐patient relationship. Discussion: The most salient aspect of the care that birthworkers of color provide is their culturally centered approach. This approach and all subsequent themes suggest that achieving birth equity for pregnant African American people starts by acknowledging and honoring their sociocultural experiences.